Heidegger's being : the shimmering unfolding - Capobianco, Richard, 1957- (New studies in phenomenology and hermeneutics (Toronto, Ont.), 2022)
"This collection of diverse essays represents a unified, perceptive look into seminal ideas of Heidegger's lifelong attention to the question of Being, and suggests some thought-provoking attempts, philosophical ventures, to go beyond them, to think them through in a new way, to deepen and expand their understanding. It offers an initial, balanced, measured, well-targeted Socratic response (cross-examination) to the hermeneutic closure imposed on them (on his texts), at least by some ideological and pre-fixed hermeneutical assumptions and prejudices, by short-circuiting the hard, scholarly labor with the texts themselves, with the writings of the philosophers in question. The clear, short, interconnected discussions of Heidegger's insights, focused on Being and based on his lectures, coalesce into a unified exposition and grasp of his multi-dimensional thinking; they prepare the ground for their questioning, for expanding the range of their understanding. The lucidity of writing, its dexterity and fluency (flux), combined with scholarly diction and terminology, enhanced by Capobianco's attunement (sensitivity) to Heidegger's language, indispensable for grasping his thought, render the manuscript (book-proposal) at hand suitable for beginners and daring, curious readers, for scholars in many fields and for "generalists" as well."--